Agronomic and nutritional evaluation of african star grass-based pastures (Cynodon nlemfuensis) in the region of Monteverde, Puntarenas, Costa Rica. I. Dry matter yield and phenology. - Villalobos, Luis (2013)
Dry matter yield and phenology of african star grass (Cynodon nlemfuensis)- based pastures were evaluated in 4 commercial dairy farms nearby to the region of Monteverde (latitude 10°20’ N, longitude 84°50’ W, 800 to 1200 masl) every other month during a two-year period. Average dry matter yield and phenological stage were 4484 kg.ha-1.grazing-1 cycle and 7.36 green leaves per regrowth, respectively. Botanical composition of pastures was 86.81% african star grass, 2.52% other grasses, 1.39% legumes, 1.53% weeds and 7.75% senescent material. Dry matter availability was higher in farms with Pacific Ocean climatic influence and decreased in the rainiest months. The phenological stage of the african star grass is between 6 to 8 green leaves per regrowth, allowing for an adequate recovery of the plant, and decreased in months with excessive precipitation.